QUALITATIVE EVALUATION OF THE URBAN VEGETATION IN BENTO GONÇALVES CITY, RS. - Santos, Nara Rejane Zamberlan dos (2003)
A survey conducted in centric streets of Bento Gonçalves city permited to evaluate the conditions of the urban arboreus vegetation. The physical and sanitary aspects was considered as “good” and no damage to the sidewalks was observed since the plants have deep roots. Most of the plants (51,7 %) was not placed under electric wires however branch cutting is a frequent practice.